Bacillus thuringiensis Cry5B protein is highly efficacious as a single-dose therapy against an intestinal roundworm infection in mice. - Yan Hu; Sophia B Georghiou; Alan J Kelleher; Raffi V Aroian (Public Library of Science (PLoS), 2010)
Intestinal parasitic nematode diseases are one of the great diseases of our time. Intestinal roundworm parasites, including hookworms, whipworms, and Ascaris, infect well over 1 billion people and cause significant morbidity, especially in children and pregnant women. To date, there is only one drug, albendazole, with adequate efficacy against these parasites to be used in mass drug administration, although tribendimidine may emerge as a second. Given the hundreds of millions of people to be treated, the threat of parasite resistance, and the inadequacy of current treatments, new anthelmintics are urgently needed. Bacillus thuringiensis (Bt) crystal (Cry) proteins are the most common used biologically produced insecticides in the world and are considered non-toxic to vertebrates.Here we study the ability of a nematicidal Cry protein, Cry5B, to effect a cure in mice of a chronic roundworm infection caused by the natural intestinal parasite, Heligmosomoides bakeri (formerly polygyrus). We show that Cry5B produced from either of two Bt strains can act as an anthelmintic in vivo when administered as a single dose, achieving a approximately 98% reduction in parasite egg production and approximately 70% reduction in worm burdens when delivered per os at approximately 700 nmoles/kg (90-100 mg/kg). Furthermore, our data, combined with the findings of others, suggest that the relative efficacy of Cry5B is either comparable or superior to current anthelmintics. We also demonstrate that Cry5B is likely to be degraded quite rapidly in the stomach, suggesting that the actual dose reaching the parasites is very small.This study indicates that Bt Cry proteins such as Cry5B have excellent anthelmintic properties in vivo and that proper formulation of the protein is likely to reveal a superior anthelmintic.